2020
DOI: 10.1111/1755-0998.13264
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput sequencing of 5S‐IGS in oaks: Exploring intragenomic variation and algorithms to recognize target species in pure and mixed samples

Abstract: Measuring biological diversity is a crucial but difficult undertaking, as exemplified in oaks where complex patterns of morphological, ecological, biogeographical and genetic differentiation collide with traditional taxonomy, which measures biodiversity in number of species (or higher taxa). In this pilot study, we generated high‐throughput sequencing amplicon data of the intergenic spacer of the 5S nuclear ribosomal DNA cistron (5S‐IGS) in oaks, using six mock samples that differ in geographical origin, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 101 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…Availability of High-Throughput Sequencing (HTS) approaches is now boosting new efforts into research questions that were previously considered too expensive and labour-intensive (Babik et al, 2009;Glenn, 2011). In a recent study, Piredda et al (2021) generated HTS amplicon data of the nontranscribed intergenic spacers of the 5S rDNA in Quercus (Fagaceae) and demonstrated the great value of this approach to provide phylogenetic information for inspecting range-wide evolutionary patterns while circumventing previous technical limitations (e.g. cloning, abundant samples, special methodological frameworks; Denk and Grimm, 2010;Simeone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Availability of High-Throughput Sequencing (HTS) approaches is now boosting new efforts into research questions that were previously considered too expensive and labour-intensive (Babik et al, 2009;Glenn, 2011). In a recent study, Piredda et al (2021) generated HTS amplicon data of the nontranscribed intergenic spacers of the 5S rDNA in Quercus (Fagaceae) and demonstrated the great value of this approach to provide phylogenetic information for inspecting range-wide evolutionary patterns while circumventing previous technical limitations (e.g. cloning, abundant samples, special methodological frameworks; Denk and Grimm, 2010;Simeone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In F. japonica, the longer, GC-rich O-type and shorter, GC-normal I-type, represent two highly divergent, only distantly related lineages; their divergence (Table 1) parallels that between subgenera of oaks Simeone et al, 2018;Piredda et al, 2021 for first HTS data) and between genera in Betulaceae (Forest et al, 2005). Both types are abundant:…”
Section: S-igs Divergence and Paralogy/homeologymentioning
confidence: 92%
“…Amplicon sequencing of loci with high information content (target sequencing) substantially reduces costs, as it makes cloning unnecessary and many individuals can be combined in the same sequencing run (Ekblom & Galindo, 2010). In a recent study, Piredda et al (2021) analysed 5S-IGS HTS amplicon data generated for Quercus (Fagaceae) and demonstrated the great potential of this technique for inspecting range-wide diversity patterns and for assessing interand intra-species relationships. In the present study, we explored the applicability of the same experimental pathway in six geographic samples of the core group of 'subgenus Fagus': the F. crenata -F. sylvatica s.l.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the detected variation may result in the identification of species-specific traits and complex evolutionary signals such as hybridization, introgression, and polyploidization, e.g., [ 50 , 51 , 52 ]. A couple of recent studies have generated HTS amplicon data of the nuclear 5S spacers to improve the efficiency of signal detection and demonstrated the high potential of the technique to inspect diversity patterns and infer evolutive pathways in highly complex species systems such as Fagaceae Dumort [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%